2021
DOI: 10.4185/rlcs-2021-1500
|View full text |Cite
|
Sign up to set email alerts
|

Pandemia y guerra: narrativas de crisis y liderazgo. Análisis de las estrategias discursivas presidenciales en el inicio de la pandemia del COVID-19

Abstract: Introducción. Las crisis provocadas por acontecimientos imprevistos como el COVID-19 ponen a prueba las capacidades de comunicación y liderazgo de los actores políticos. Como respuesta, estos políticos establecen estrategias comunicativas que buscan redefinir y reforzar su liderazgo (y su imagen) ante la opinión pública. Metodología. Este texto analiza el desarrollo de algunas de las estrategias llevadas a cabo por los líderes políticos de los tres países europeos más afectados en la primera ola de la pandemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The largest cluster (in red) includes 23 items and is mainly related to crisis response strategies, strategic communication, situational crisis communication, and communication on social media. The linkages to terms such as image repair, internal communication, and corporate communication may indicate that crisis communication concerns related to organizations can provide multiple cobenefits and strengthen public relations (Coombs, 2021;Tornero et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest cluster (in red) includes 23 items and is mainly related to crisis response strategies, strategic communication, situational crisis communication, and communication on social media. The linkages to terms such as image repair, internal communication, and corporate communication may indicate that crisis communication concerns related to organizations can provide multiple cobenefits and strengthen public relations (Coombs, 2021;Tornero et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Few papers have intensively reviewed crisis communication during the pandemic and infectious disease outbreaks (MacKay et al, 2022;Malecki et al, 2021;Sadri et al, 2021) or captured risk and disaster communication (Bradley et al, 2014;Goerlandt et al, 2020). Lately, the focus has shifted toward using virtual channels and space (Eriksson, 2018;Liu-Lastres, 2022;Tornero et al, 2021;Wang and Dong, 2017;Yang, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In their semiotic analysis of the speeches of Italian, French, and Spanish presidents during the pandemic [27], concluded that the political leaders discursively used the relationship between science and politics to strengthen or justify the strategies chosen. [22] analyzed the Dutch Prime Minister's press conferences and the related Twitter responses in the first stage of the pandemic.…”
Section: Science and Politics During The Covid-19 Pandemicmentioning
confidence: 99%
“…According to the research of José Manuel Pérez Tornero, they have explained that when the public of a country is threatened by external factors such as the epidemic, the leadership of the government and national leaders will play a vital role The determination, faith, and dedication of good leaders will lead the people to overcome the epidemic in all aspects, and overcome the rumors of the epidemic. However, in addition to individual heroism, how to generally improve the government’s ability to refute rumors is a very important link in the prevention and control of epidemic rumors ( Pérez Tornero et al, 2021 ). Ciara M finds that no effects have been formed by providing a general warning about the dangers of the fake stories, regardless of the framing of the warning in positive or negative terms ( Greene & Murphy, 2021 ).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%